Quality Enhancement of AC Chopper Using Genetic Algorithm - S. Mahendran; Gnanambal I; Maheswari A (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
This paper mainly deals with the design of AC chopper using Genetic Algorithm based harmonic elimination technique. Genetic Algorithm is used to calculate optimum switching angles to eliminate lower order harmonics in the output voltage. Total Harmonic Distortion of output voltage is calculated from the obtained switching angles and also adopted in the proposed fitness function. Comparative analysis is made for the switching angles obtained by the Newton Raphson method and the proposed Genetic Algorithm. The analysis reveals that the proposed technique is on par with conventional method. Additionally, the Genetic Algorithm approach offers less computational burden, guaranteed global optima in most cases and faster convergence. The proposed method is simulated in Matlab/Simulink model and the results shows that the proposed method works with high effectiveness, accuracy and rapidity.